Systematic review and meta-analysis of cardiac involvement in mitochondrial myopathy. (August 2019) - Quadir, Asfia; Pontifex, Carly Sabine; Lee Robertson, Helen; Labos, Christopher; Pfeffer, Gerald
Abstract : Objective: Our goal was to perform a systematic review of the literature to demonstrate the prevalence of cardiac abnormalities identified using cardiac investigations in patients with mitochondrial myopathy (MM). Methods: This systematic review surveys the available evidence for cardiac investigations in MM from a total of 21 studies including 825 participants. Data were stratified by genetic mutation and clinical syndrome. Results: We identified echocardiogram and ECG as the principal screening modalities that identify cardiac structural (29%) and conduction abnormalities (39%) in various MM syndromes. ECG abnormalities were more prevalent in patients with m.3243A>G mutations than other gene defects, and patients with mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) had a higher prevalence of ECG abnormalities than patients with other clinical syndromes. Echocardiogram abnormalities were significantly more prevalent in patients with m.3243A>G or m.8344A>G mutations compared with other genetic mutations. Similarly, MELAS and MERRF had a higher prevalence compared with other syndromes. We observed a descriptive finding of an increased prevalence of ECG abnormalities in pediatric patients compared with adults. Conclusions: This analysis supports the presence of a more severe cardiac phenotype in MELAS and myoclonic epilepsy with ragged red fibres syndromes and with their commonly associated genetic mutations (m.3243A>G and m.8344A>G). This provides the first evidence basis on which to provide more intensive cardiac screening for patients with certain clinical syndromes and genetic mutations. However, the data are based on a small number of studies. We recommend further studies of natural history, therapeutic response, pediatric participants, and cardiac MRI as areas for future investigation.